Adiponectin is decreased in bipolar depression. (26th November 2019) - Platzer, Martina; Fellendorf, Frederike T.; Bengesser, Susanne A.; Birner, Armin; Dalkner, Nina; Hamm, Carlo; Hartleb, Riccarda; Queissner, Robert; Pilz, René; Rieger, Alexandra; Maget, Alexander; Mangge, Harald; et al.
Abstract: Objectives: Bipolar disorder (BD) is often accompanied by medical comorbidities, which affect illness course and prognosis. Adipokines may not only be involved in the aetiopathogenetic mechanisms of these comorbidities; there might be an association between adipokines and the neuropsychiatric core features of BD such as mood disturbances and cognitive deficits. Methods: In this investigation, fasting blood samples from 120 individuals with BD (75 euthymic and 45 with mild depressive symptoms) and 68 control subjects were taken and adiponectin and leptin concentrations were analysed. Results: We found that, in female participants, adiponectin levels differed significantly between patients and controls indicating lower levels in individuals with BD, even after controlling for BMI ( F (1, 92) = 4.65, P = 0.034, partial η 2 = 0.05). After stratification by mood status we found a significant difference in adiponectin between controls, euthymic and depressive patients ( F (2, 180) = 4.90, P = 0.008, partial η 2 = 0.05). Conclusions: This investigation confirms previous findings of an association between low adiponectin levels and depressive state in individuals with BD. Beyond its immediate effect on central nervous system function, adiponectin might interfere with pathophysiological mechanisms of BD and its somatic comorbidities via involvement in metabolic and inflammatory processes.